0200 The Effectiveness Of Caffeine Gum In Reducing Sleep Inertia Following A 30min Nighttime Nap Opportunity: Preliminary Results. (27th April 2018) - Centofanti, S A; Dorrian, J; Grant, C; Stepien, J; Coates, A; Lushington, K; Evans, A; Reuter Lange, S; Banks, S
Abstract: Introduction: Many shiftworkers take short naps on nightshift to reduce the detrimental effects of sleep loss. However, sleep inertia resulting from napping can have deleterious effects on performance. Caffeine may be a useful countermeasure for sleep inertia. This study examined the effectiveness of 200mg caffeine gum in reducing sleep inertia following a 30min nighttime nap opportunity at 0200h. Methods: N =5 subjects (3F, M=22.2±SD3.8y) took part in a 2-day laboratory study, with a randomised double-blind, placebo-controlled crossover design following one-week abstaining from caffeine consumption. The study involved one simulated nightshift with a 30min nap opportunity at 0200h. Immediately after waking from the nap, subjects were administered caffeinated gum or placebo gum. Subjects undertook a 3min psychomotor vigilance task (PVT) at 10min pre-nap (0150h) and 5, 15, 25 and 35min post-wakeup. Subjects returned one-week later to undertake the alternate caffeine/placebo condition. Linear mixed model ANOVA assessed differences in PVT lapses (response times >355msec) between caffeine and placebo conditions post-nap. Planned contrasts were conducted to assess differences in each post-nap PVT trial (5, 15, 25, 35min) compared to pre-nap (0150h). Results: There was a significant main effect of condition (F1, 37 =23.06, p <0.001), with fewer lapses post-nap in the caffeine condition (M=11.9, SE=4.4) compared to placebo (M=18.7, SE=4.5 lapses), but no significant effect of trial or condition*trial interaction. Planned contrasts revealed that compared to pre-nap, there were significantly more lapses at 25- and 35min ( p <0.05) post-nap in the placebo condition, but no differences in the caffeine condition ( p >0.05). Conclusion: Following a 30min nap opportunity at 0200h, 200mg of caffeinated gum attenuated performance decrements that were apparent from 25- to 35min post-wakeup in the placebo condition. Caffeine gum may be an effective countermeasure for mitigating performance deficits on nightshift, and appears to take 15-25min to take effect. Future analyses should investigate whether the alerting effects of caffeine gum also protect against performance deficits following longer and/or later nap opportunities, and whether any benefits last towards the end of the nightshift. Support (If Any): University of South Australia